1989
DOI: 10.1007/bf01403497
|View full text |Cite
|
Sign up to set email alerts
|

A new ultrasound-guided brain biopsy technique through a burr hole

Abstract: There is a disadvantage in brain biopsy by ultrasonic guidance comparing it with the CT guided approach. It is the fact that the ultrasonic method requires a small craniotomy or multiple trephinations because the size of the transducer exceeds the diameter of the burr hole and the echographic information from the trocar which houses the biopsy forceps, becomes poor when the sound beams run nearly parallel with the site of its insertion. The authors devised a brain biopsy technique through only one burr hole un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The experimental basis was given by Enzmann et al who clearly demonstrated that ultrasound imaging is able to detect abscesses in all stages of evolution [13]. Miniaturized ultrasound probes were developed in the late 1980s and used for biopsy of tumors and evacuation of cerebral hematomas [15,22]. Moringlane et al used a similar probe like ours to survey frame-based stereotactic procedures and clearly demonstrated sufficient quality of imaging although image resolution tended to be relatively poor at distances longer than 60 mm due to the limited acoustic aperture of the probe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental basis was given by Enzmann et al who clearly demonstrated that ultrasound imaging is able to detect abscesses in all stages of evolution [13]. Miniaturized ultrasound probes were developed in the late 1980s and used for biopsy of tumors and evacuation of cerebral hematomas [15,22]. Moringlane et al used a similar probe like ours to survey frame-based stereotactic procedures and clearly demonstrated sufficient quality of imaging although image resolution tended to be relatively poor at distances longer than 60 mm due to the limited acoustic aperture of the probe.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this consecutive technique did not allow real-time imaging of the procedure. This was achieved by Tsutsumi et al in 1989 with a round ultrasound probe of 12 mm [15] and finally Moringlane et al demonstrated real-time ultrasound imaging of frame-based stereotactic procedures using a probe with tip dimensions of 8 8 mm [16]. The question of this study is whether it is possible to safely localize and aspirate brain abscesses under ultrasound guidance alone using a probe that is small enough to allow a single standard burr hole approach.…”
Section: Introductionmentioning
confidence: 88%
“…Initially they were fixed to the bone. With current fixers fastened to the operation table, this shortcoming is excluded [9].…”
Section: Discussionmentioning
confidence: 99%
“…Bone aspirates are now commonly performed in our practices. [33][34][35][36][37][38][39][40][41][42] A craniotomy or burr hole permits transducer placement on the dura or cortical surface. 55 Radiographic evidence of a destructive or destructive-productive bone lesion was identified in the appendicular skeleton of 20 animals and in the axial skeleton of 3.…”
Section: Bonementioning
confidence: 99%